Determinants of Personal Protective Equipment Compliance Among Ship Workers at Trisakti Port, Banjarmasin: A Cross-Sectional Study - Chairiyanti Chairiyanti; Eko Suhartono; Silvia Kristanti Tri Febriana; Nelly Al Audhah; Meitria Syahadatina Noor (Lambung Mangkurat University, 2025)
This study aims to analyze the factors that influence crew members' use of Personal Protective Equipment (PPE) at Trisakti Port, Banjarmasin. The method used is quantitative research with a cross-sectional approach involving 107 crew members selected using the Slovin formula and proportional random sampling technique. The data was collected through questionnaires tested for validity and reliability and observation sheets. Data analysis used Fisher's Exact Test and logistic regression to determine the dominant factors influencing compliance with PPE. The results showed that leadership supervision, company policies, and self-efficacy significantly affected the behavior of using PPE, with leadership supervision being the most dominant factor. Crew members routinely supervised were 102.8 times more likely to comply with PPE than those not supervised. In addition, clear policies and high self-efficacy also played an essential role in increasing compliance. Although the perception of obstacles did not have a significant effect, PPE's comfort and suitability factors still need to be considered. This study suggests that companies strengthen supervision, implement consistent policies, and increase crew independence through ongoing training to create a safe and productive work environment.